1997
DOI: 10.1007/bf03013000
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of activated neutrophils by a filter during cardiac valve surgery

Abstract: Depletion of activated neutrophils by a filter during cardiac valve surgeryPurpose: To determine whether inclusion of a neutrophil-speciflc filter into the extracorporeal circuit during open heart valve surgery alters postoperative outcomes.Methods: Convenience sampling of 24 patients undergoing elective open heart valve surgery between July 1993 and June 1994. Patients were randomized to a neutrophil-specific filter (n= I I) orto a standard blood filter (n= 13) during cardiopulmonary bypass.Results: Neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
(4 reference statements)
2
25
1
1
Order By: Relevance
“…IL-1, IL-6, IL-8 and TNF) during or after cardiac surgery [22,23,39,46,50,55]. The only study to show a significant effect utilized a venous line leukodepleting filter [10] and observed a significant decrease in IL-8 compared to controls.…”
Section: Does Systemic Leukofiltration Reduce Markers Of Systemic Infmentioning
confidence: 87%
See 3 more Smart Citations
“…IL-1, IL-6, IL-8 and TNF) during or after cardiac surgery [22,23,39,46,50,55]. The only study to show a significant effect utilized a venous line leukodepleting filter [10] and observed a significant decrease in IL-8 compared to controls.…”
Section: Does Systemic Leukofiltration Reduce Markers Of Systemic Infmentioning
confidence: 87%
“…In a study that included only three patients (one filtered and two controls), Thurlow et al observed a gradient in the expression of CD11a and CD45RO across the filter not seen in the two control patients and also claimed that the filter selectively removed activated leukocytes [40]. The effect of filtration on CD-11b expression appears to be variable, with no difference [27,39], downregulation [51] and up-regulation of CD-11b [48] all having been reported. In a clinical study on patients undergoing CABG surgery by Chen et al [52], L-selectin, P-selectin, ICAM-1 and PECAM-1 were all significantly reduced by leukofiltration.…”
Section: Does Systemic Leukofiltration Reduce Markers Of Systemic Infmentioning
confidence: 88%
See 2 more Smart Citations
“…In the clinical field, one study reported reduced expression of the CD18 surface adhesion molecule after use of arterial line leucocyte filtration in patients undergoing heart valve operations [12]. A more recent report described a significant reduction in the expression of the adhesion molecules CD11b and L-selectin with continuous arterial line leucocyte depletion in CABG surgery [13].…”
Section: Activated White Cell Countsmentioning
confidence: 97%